Lecturers’ perception toward students entrepreneurial attitudes / Nur Huda Mohammad Tohar & Nur Suhaila Amira Shafee - Mohammad Tohar, Nur Huda; Shafee, Nur Suhaila Amira (Faculty of Hotel and Tourism, Universiti Teknologi MARA,Terengganu, 2018)
The purpose of this study is to determine the factors that contribute into students’ entrepreneurial attitudes and identify lecturers’ perceptions regarding students with entrepreneurial attitudes. This paper seeks for a better understanding on how students having entrepreneurial attitudes affect the lecturers’ perception. A collection of secondary data was used for analyzation of results, regarding students’ entrepreneurial attitudes and how it reflects the perception from lecturers. Factors like demographic characteristics, previous entrepreneurial experiences and entrepreneurship education are commonly influenced students behaviour to venture in entrepreneurship. Through the compare and contrast of data gained, the research results showed that demographic characteristics in term of family background are not highly affected student’s attitude whereas previous entrepreneurial experiences and entrepreneurship education do affect student’s attitude towards entrepreneurship. As for lecturer’s perception, they give positive perception on students’ entrepreneur. This is because the lecturers believed that the students able to help themselves to be job creators instead of job seekers in the future. Although students who get involved with entrepreneurship while studying can give negative effects to their academic performance, students can prevent it by dividing their time equally between working and studying.